Onderweg na ’n teksgebaseerde retoriese analise van Paulus se briewe - Snyman, AH (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Towards a text-centred rhetorical analysis of Paul’s letters The pioneering commentary of HD Betz on Galatians has been met with mixed reaction. A number of scholars responded favourably to his proposal of analysing a Pauline letter in terms of categories developed in ancient rhetoric for the creation of forensic speeches. Others felt uneasy about the rigid way in which he applied these categories to Galatians and suggested alternative approaches. When more scholars – especially classicists – entered the debate in the 1990’s and revealed the weak foundations of these approaches, the time was ripe for an approach in which the letter itself serves as the starting point for analysis and not any ancient rhetorical model from outside. The aim of this article is to describe the process of developing a text-centred approach to rhetorical analysis. A proposal for such an approach is summarised and critically evaluated by comparing it with Betz’s analysis. It is suggested that the proposal be applied to all Paul’s letters in order to develop a thoroughly grounded Pauline rhetoric in due course.